A Note on Diversity of Aquatic Insects in Rivers of Royal Belum State Park, Perak (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Royal Belum State Park is one of the oldest, protected and pristine land masses that joins hundreds of small tributaries that feed Lake Temenggor. A scientific expedition was conducted, and the diversity of aquatic insects was studied. Five rivers namely Sungai Ta Ng, Sungai Papan, Sungai Gen, Sungai Ruok and Sungai Rambutan were chosen. A kick-sampling technique was deployed to collect the aquatic insect larvae. The study recorded a total of 42 families and 61 genera of aquatic insects which Sungai Papan has the largest number of taxa recorded (18 families, 26 genera). The number of intolerant taxa (Ephemeroptera, Plecoptera, Trichoptera; EPT) in Sungai Papan was substantial (15 genera). Odonata was discovered to be the most diverse order (13 genera), followed by Ephemeroptera (10 genera) and Trichoptera (10 genera). The findings provided a concise richness of aquatic insects, which might serve as a good tool for evaluating the conservation needs of the area.
Keywords: macroinvertebrate; river ecosystem; richness; taxa